Type A thymoma with simultaneous solitary intrapulmonary metastasis: A case report - Tatematsu, Tsutomu (Thorac Cancer, 2021)
A 79‐year‐old woman was referred to our facility because of an abnormal chest shadow. Chest computed tomography (CT) showed a solitary right middle lung nodule with a maximum diameter of 3 mm and anterior mediastinal nodule with a maximum diameter of 21 mm. The lung nodule was suspected of being a primary lung cancer rather than a metastatic tumor because there were no primary malignant tumors, apart from an anterior mediastinal tumor visible on diagnostic imaging, including F(18) fluorodeoxyglucose‐positron emission tomography, and a solitary lung nodule. Partial lung resection by video‐assisted thoracoscopic surgery (VATS) was performed, and the intraoperative frozen section of the tumor tissue resulted in a diagnosis of carcinoid tumor. As a result, right middle lobectomy by VATS was performed. The final histological diagnosis of the permanent specimen was intrapulmonary type A thymoma. VATS thymectomy was performed three months later. The histological diagnosis was type A thymoma with intrapulmonary metastasis (Masaoka stage IVb). Additional therapy was not performed because complete resection was achieved. Follow‐up CT was performed once every six months after the operation. The patient has been followed up for one year without any further recurrence.